Clofazimine is a broad-spectrum coronavirus inhibitor that antagonizes SARS-CoV-2 replication in primary human cell culture and hamsters - Yuan, Shuofeng (Res Sq, 2020)
COVID-19 pandemic is the third zoonotic coronavirus (CoV) outbreak of the century after severe acute respiratory syndrome (SARS) in 2003 and Middle East respiratory syndrome (MERS) since 2012. Treatment options for CoVs are largely lacking. Here, we show that clofazimine, an anti-leprosy drug with a favorable safety and pharmacokinetics profile, possesses pan-coronaviral inhibitory activity, and can antagonize SARS-CoV-2 replication in multiple in vitro systems, including the human embryonic stem cell-derived cardiomyocytes and ex vivo lung cultures. The FDA-approved molecule was found to inhibit multiple steps of viral replication, suggesting multiple underlying antiviral mechanisms. In a hamster model of SARS-CoV-2 pathogenesis, prophylactic or therapeutic administration of clofazimine significantly reduced viral load in the lung and fecal viral shedding, and also prevented cytokine storm associated with viral infection. Additionally, clofazimine exhibited synergy when administered with remdesivir. Since clofazimine is orally bioavailable and has a comparatively low manufacturing cost, it is an attractive clinical candidate for outpatient treatment and remdesivir-based combinatorial therapy for hospitalized COVID-19 patients, particularly in developing countries. Taken together, our data provide evidence that clofazimine may have a role in the control of the current pandemic SARS-CoV-2, endemic MERS-CoV in the Middle East, and, possibly most importantly, emerging CoVs of the future.